«ГҮЛНАРА» ҲӘМ «ЖАМАН БАЛА» (Б.Қайыпназаровтың «Гүлнара» ҳәм Т.Мәтмуратовтың «Гүл қыстырсам сүмбил шашыңа» қосықларының халық қосықларына айланыў өзгешеликлери) - Баўатдинова, C. (SCIENCE and SOCIETY, 2022)
Convesion features of songs by B.Kaypnazarov "Gulnora" and T.Matmuratov «Gul kistirsan sumbil shashina» / Plaint with flowers («Jaman bala» / Bad boy) into folk songs is deeply analysed, moreover. From motive "Waiting sweet-heart» is depicted issues of creating mastery lyric heroic charaster «Jaman bala» and some issues of contectual concepts. From lingua-poetic point of view text of song shows masterly usage of works in text.
Keywords: motive; lyrical hero; concept; text; redif; national color; rhetoric; character; dialogue; monologue